Artificial intelligence in education: Current challenges - Fabijanić Gagro Sandra (Anali Pravnog Fakulteta u Beogradu)
Artificial intelligence has already led to changes in education, and its influence will continue to grow. However, its implementation in education is not just about introducing new technologies - it requires reflection and the introduction of new educational practices, ethical considerations and the essential strengthening of critical thinking to properly evaluate the reliability of sources and the accuracy of information offered by artificial intelligence. This paper aims to highlight the positive and negative aspects of the use of artificial intelligence in education, focusing on the current challenges, especially ethical and legal ones. The regulatory environment in this field is becoming increasingly dynamic, either through the adaptation of existing or the adoption of new comprehensive laws and legal frameworks at both the national and international levels, to ensure the ethical, non-discriminatory, sustainable and verifiable use of artificial intelligence in education.